ip100805_elic_VerbalForms_oor_3 - Ирина Пайковна Кошкарёва (Туглакова); Олеся Ханина (Bernard Comrie, 2010)
О.Ханина собирает с И.П.Кошкаревой основные формы глагола звонкочередующегося класса oor 'есть' (см. набор форм в verbalMorphology_Tundra_todo2010.doc), часть 3 O.Khanina collects with I.P.Koshkarjova main forms of a voiced alternating verb oor 'to eat (ipfv)' (see the list of forms in verbalMorphology_Tundra_todo2010.doc), part 3 Language_Name: Enets Language_Region: Asia Language_Country: Russia Project_Status: Complete Year: 2007 Start_Date: 2008-02-01 End_Date: 2011-01-31 Title ip100805_elic_VerbalForms_oor_3